DEVELOPMENT OF PROBLEM-BASED LEARNING-BASED LEARNER WORKSHEETS (LKPD) ON THE SUBJECT OF HOOKE'S LAW AT SCHOOL MAS PLUS AL-ULUM MEDAN - Safitri, Eka (Universitas Negeri Medan, 2023)
This study aims to determine the level of feasibility of Problem Based Learning based LKPD on Hooke's Law material based on material experts and media experts, and to determine the level of practicality of Problem Based Learning based LKPD on Hooke's Law material based on the response of teachers in the field of study and student responses. This research uses research and development methods or Research and Development (R&D). The LKPD feasibility test uses a Likert scale questionnaire validated by two validators. And the practical test of LKPD was carried out at MAS Plus Al-Ulum Medan school by teachers and students. Based on the results of the study, a material expert validator assessment of 72% was obtained, a media expert assessment of 80% with feasible / valid criteria. And based on the response of the physics teacher, a score of 94% was obtained, and the response of students obtained a value of 94.45% with very practical criteria.